2018
DOI: 10.14238/pi58.1.2018.42-7
|View full text |Cite
|
Sign up to set email alerts
|

The addition of omeprazole to ondansetron for treating chemotherapy-induced nausea and vomiting in pediatric cancer patients

Abstract: Background Chemotherapy-induced nausea and vomiting are some of the most disturbing side effects in pediatric cancer patients. The standard recommendation is the use of 5-hydroxytryptamine 3 receptor antagonist, such as ondansetron, to treat these symptoms. Despite this treatment, more than 50% of patients still experience nausea and vomiting.Objective To evaluate the effect of the addition of omeprazole to ondansetron in the treatment of chemotherapy-induced nausea and vomiting.Methods A double-blind, randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Its quick IV administration results ototoxocity. 8,9 Matsota et al 10 reported 1% extrapyramidal side effect of metoclopramide but witnessed its 85% significance in reducing residual gastric fluid volume when it was administer IV 15-30 minutes prior to surgery. H2 receptor antagonism is action mechanisms of ranitidine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its quick IV administration results ototoxocity. 8,9 Matsota et al 10 reported 1% extrapyramidal side effect of metoclopramide but witnessed its 85% significance in reducing residual gastric fluid volume when it was administer IV 15-30 minutes prior to surgery. H2 receptor antagonism is action mechanisms of ranitidine.…”
Section: Introductionmentioning
confidence: 99%
“…For treating gastro-esophageal reflux syndrome, omeprazole is used which is a proton pump. Simbolon et al 9 conducted a double randomized controlled trial by adding omeprazole to ondansetron for avoiding vomiting and nausea after chemotherapy. The failure ratio was 18% in ondansetron-omeprazole group while in ondansetronplacebo group it was 50% p-value = 0.01.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that eye-surgery is associated with an increased risk of PONV about 20% to 40% (2,3). PONV is a very distressing outcome, which may lead to medical complications such as wound disruption, esophageal tears, gastric herniation, fatigue, dehydration, possibly electrolyte imbalances, and lung aspiration (4)(5)(6). There are some factors affecting postoperative nausea and vomiting such as age, sex, obesity (BMI > 30 kg/m 2 ), anxiety, gastroparesis (following anesthesia and analgesia), hypoglycemia, and vasoactive medications (1,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Today, a large number of methods are available for controlling nausea and vomiting, such as drug therapy and complementary therapies (1,5). Choosing and prescribing appropriate medical or complementary therapies used beside pharmacological methods significantly improve the quality of life and performance of the patients and result in beneficial effects (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation